Imagination, creativity, and responsible management in the fourth industrial revolution - Fields, Ziska 1970-; Bucher, Julien 1985-; Weller, Anja 1985- (IGI Global, 2019)
"This book explores how human imagination and creativity can be used to develop responsible and sustainable management in the fourth industrial revolution to develop more opportunities for humans to thrive"--
Description based on title screen (IGI Global, viewed 08/13/2019)
Keywords: Management; Creative ability in business; Social responsibility of business